Supply chain development: Criterion of decision for implementation of future seed collection centers in rural areas - Boris Gerardo German; Edward Jiménez; Andrés Chico; Sebastián Espinoza; Ricardo A. Narváez C. (Revista Tecnológica)
The present work aims to provide an optimization model as a selection criterion for approving new Jatropha Curcas collection points in rural areas.  Field work was carried out for characterizing the collection points, to establish the local Jatropha supply and to determine transportation costs. Data were complemented whit a Geographical Information System (GIS) and an objective function was defined in order to determine the Jatropha oil production-associated profit. The supply chain was optimized in order to maximize the profits and a sensitivity analysis was performed so as to find a profit-based criterion for the acceptance of future collection points.  There are collection centers empirically implemented, that due to social components, can’t be removed or displaced. This constitutes the starting point for this logistic model. The location of collection points and the amount of collected Jatropha are the strategic variables that determine the standard deviation, and the more disperse the values, the higher the standard deviation and the stricter the acceptance criteria for evaluating new collection points. The transport cost of Jatropha Curcas seed is affected because it´s a secondary activity for farmers. The principal production activity is maize. The economic development and the social growth of the population in rural areas are the reason why the existent seed collection centers aren’t removed